Comparison of the microbial composition of African fermented foods using amplicon sequencing - Diaz, Maria; Kellingray, Lee; Akinyemi, Nwanneka; Olaoluwa Adefiranye, Oyetayo; Houngbédji, Marcel; Kamya, Deus; Muzira Mukisa, Ivan; Obodai, Mary; Mayer, Melinda J.; Oguntoyinbo, Folarin A.; Narbad, Arjan (Scientific reports, 2019)
Fermented foods play a major role in the diet of people in Africa, where a wide variety of raw materials are fermented. Understanding the microbial populations of these products would help in the design of specific starter cultures to produce standardized and safer foods. In this study, the bacterial diversity of African fermented foods produced from several raw materials (cereals, milk, cassava, honey, palm sap, and locust beans) under different conditions (household, small commercial producers or laboratory) in 8 African countries was analysed by 16S rRNA gene amplicon sequencing during the Workshop “Analysis of the Microbiomes of Naturally Fermented Foods Training Course”. Results show that lactobacilli were less abundant in fermentations performed under laboratory conditions compared to artisanal or commercial fermentations. Excluding the samples produced under laboratory conditions, lactobacilli is one of the dominant groups in all the remaining samples. Genera within the order Lactobacillales dominated dairy, cereal and cassava fermentations. Genera within the order Lactobacillales, and genera Zymomonas and Bacillus were predominant in alcoholic beverages, whereas Bacillus and Lactobacillus were the dominant genera in the locust bean sample. The genus Zymomonas was reported for the first time in dairy, cereal, cassava and locust bean fermentations.
Keywords: Microbial composition; African fermented foods; Amplicon sequencing